The Cave of the Nymphs at Pharsalus: Studies on a Thessalian Country Shrine - Wagman, Robert S. (Brill Studies in Greek and Roman Epigraphy Ser, 2015)
Contents -- List of Plates, Tables, and Charts -- Acknowledgements -- Abbreviations and Other Prefatory Matters -- Introduction -- Chapter 1 Geography and Landscape (Plates I-V, VII-X) -- 1 Overview of the Pharsalian Territory -- 2 The Pharsalian Hill Country: Anatomy of a Borderland -- Chapter 2 The Site (Plates VI, VIII-XXII) -- 1 Description -- 1.1 Approach -- 1.2 The Site (Lower Level) -- 1.3 The Site (Upper Level) -- 2 Interpretation -- 2.1 Approach -- 2.2 The Sacred Garden -- 2.3 The Stairway -- 2.4 The Forecourt and Its Structures -- 2.5 The Roof -- 2.6 The Cave -- 3 Conclusions -- Chapter 3 The Votives (Plates XXV-XXXV) -- 1 Discovery -- 2 Excavations -- 3 Catalog of Objects -- 4 Appendix: Unpublished Objects -- 5 Conclusions -- 6 Charts -- Chapter 4 The Inscriptions (Plates XXIII-XXIV) -- 1 Inscription I -- 1.1 Epigraphical Overview -- 1.2 Text and Translation -- 1.3 Metrical Conspectus -- 1.4 Commentary -- 1.5 Conclusions -- 2 Inscription II -- 2.1 Epigraphical Overview -- 2.2 Text and Translation -- 2.3 Metrical and Stylistic Conspectus -- 2.4 Commentary -- 2.5 Conclusions (Pantalces: Construction of a Cult Founder) -- Conclusion -- Bibliography -- Indices -- Index of Sources -- Index of Names -- Index of Geographical Names -- Plates.